2009
DOI: 10.1002/app.29579
|View full text |Cite
|
Sign up to set email alerts
|

Influence of isomery in drug release from poly(butyl monoitaconate‐co‐acrylamide) hydrogels

Abstract: In this work, we report the synthesis and characterization of poly(butyl monoitaconate-co-acrylamide) hydrogels to be used as drug release agents. Four isomers of butanol were used to synthesize the hydrogels. The influence of butyl monoitaconate isomery on swelling behavior, Young's and compression moduli, cross-linking density and molar mass between crosslinks are reported. It was found that by increasing butyl ramification, equilibrium degree of swelling, and the time for reaching swelling equilibrium decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Furthermore, it has shown that water absorbency of hydrogels linearly rises when increasing the initiator concentration while the molecular weight in polymerization by free radicals decreases. It is important to notice that in our work, the concentration range of initiator and crosslinking selected for the study (0.2–0.4%) did not allow us to observe dramatic changes in the hydrogel swelling after their modification (when maintaining constant the pH:ASS, monomers ratio, and neutralizing percentage). The combined effect of these two parameters on hydrogel swelling behavior is shown in the three‐dimensional response surface plots obtained at pH:ASS 4.0, 7.5, and 11.0 (Figure S3 of Supporting Information).…”
Section: Evaluation Of Swelling and Removal Properties Of Metal Oxidesmentioning
confidence: 83%
“…Furthermore, it has shown that water absorbency of hydrogels linearly rises when increasing the initiator concentration while the molecular weight in polymerization by free radicals decreases. It is important to notice that in our work, the concentration range of initiator and crosslinking selected for the study (0.2–0.4%) did not allow us to observe dramatic changes in the hydrogel swelling after their modification (when maintaining constant the pH:ASS, monomers ratio, and neutralizing percentage). The combined effect of these two parameters on hydrogel swelling behavior is shown in the three‐dimensional response surface plots obtained at pH:ASS 4.0, 7.5, and 11.0 (Figure S3 of Supporting Information).…”
Section: Evaluation Of Swelling and Removal Properties Of Metal Oxidesmentioning
confidence: 83%
“…To elucidate the mechanism of fluid diffusion into the polymer matrix during hydrogel swelling in protein solution, the diffusion exponents n were estimated using Ritger‐Peppas equation: MtM0=ktn where M t and M 0 are the amount of water absorbed by the hydrogel at time t and at equilibrium, respectively, k is a characteristic constant of the system, and n is a characteristic exponent of the mode of water transport . The value of the diffusion exponent n has been shown to be dependent on the rates of liquid diffusion into the polymer matrix and polymer relaxation . If n = 0.5 the case corresponds to the Fickian diffusion‐controlled mechanism (where the rate of water diffusion is lower than the rate of relaxation of the polymer chain); if 0.50 < n < 1, the non‐Fickian diffusion takes place (when the water diffusion and chain relaxation rates are comparable); if n < 0.5, the case is regarded as Fickian diffusion (but “less Fickian” when the water penetration rate is much below the polymer chain relaxation rate).…”
Section: Resultsmentioning
confidence: 99%
“…For the determination of the swelling rate and equilibrium (maximal achievable) water content in the hydrogel, considering that the swelling kinetics conforms to the second-order equation, the following equation was applied 41 :…”
Section: Discussionmentioning
confidence: 99%